2020
DOI: 10.3892/etm.2020.9239
|View full text |Cite
|
Sign up to set email alerts
|

<em>Aldh2</em> gene reduces oxidative stress in the bladder by regulating the NF‑&kappa;B pathway in a mouse model of ketamine‑induced cystitis

Abstract: Aldehyde dehydrogenase 2 (aldh2) serves an important role in the development of organ injury. Therefore, the present study investigated the effects of aldh2 on the oxidative stress response in a mouse model of ketamine-induced cystitis (KIC). A total of 60 8-week-old male Institute of Cancer Research wild-type (WT) mice and 45 aldh2 knock-out (KO) mice were randomized to receive low-dose ketamine (30 mg/kg), high-dose ketamine (60 mg/kg) or normal saline (controls). At 4, 8 and 12 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Clinically, abnormal ALDH2 expression contributes to a large amount of human diseases [ 27 , 28 ]. It has been reported that ALDH2 knock-out mice exhibits significantly enhanced oxidative stress and inflammation in ketamine-induced cystitis [ 7 ]. Activation of ALDH2 protects against fibrosis, apoptosis and necroptosis in primary cardiomyocytes induced by high glucose via repression of oxidative stress and inflammation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, abnormal ALDH2 expression contributes to a large amount of human diseases [ 27 , 28 ]. It has been reported that ALDH2 knock-out mice exhibits significantly enhanced oxidative stress and inflammation in ketamine-induced cystitis [ 7 ]. Activation of ALDH2 protects against fibrosis, apoptosis and necroptosis in primary cardiomyocytes induced by high glucose via repression of oxidative stress and inflammation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aldehyde dehydrogenase 2 (ALDH2), a member of the aldehyde dehydrogenase (ALDH) superfamily that has 19 ALDH subtypes, regulates aldehyde metabolism by eliminating cytotoxic aldehydes, thereby reducing oxidative stress and inhibiting the production of reactive oxygen species (ROS)-related toxic products [ 6 ]. Compelling evidence indicate that ALDH2 gene alleviates ketamine-induced cystitis in mouse model through inhibiting oxidative stress [ 7 ]. ALDH2 overexpression contributes to the reduction of ROS production and inhibit inflammation in high glucose-induced H9C2 cardiac cell injury [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, intense efforts are being made to clarify the genome‐wide association of BUC and identify more valuable candidate genes for diagnostic markers, and therapeutic targets [ 5 ]. The variants of aldehyde dehydrogenase (ALDH2) enzyme were demonstrated to be closely associated with the higher recurrence rate of BUC [ 8 ]. CD44 polymorphisms probably responding for the susceptibility of BUC were potential for a molecular prognostic marker [ 9 ].…”
Section: Introductionmentioning
confidence: 99%